Public Sphere and Dialogue Communication about Conservation in Kepulauan Seribu National Park - Swarnawati, Aminah; Saleh, Amiruddin; Ginting, Basita; Soetarto, Endriatmo; Satria, Arif (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2018)
Conservation programs in Kepulauan Seribu National Park (TNKpS) need communication space in order to attract target group participation, It is necessary for for community of fisherman to talk each regarding conservation policies addressed to.Public sphere defines asa freepolitical and economic domination elements space, existing public sphere in TNKpS have physical or non-physical characteristics, actors either co-opted or not co-opted, and their political public sphere either authentic or un-authentic.There was a two-way dialogical communicatio in public sphere. Dialogue in the public sphere was seen from five types: technical dialogue, debate, genuine dialogue, reconciliation and critical, the results show only the genuine dialogue that occurred.Five obstacles in dialogical communication did not occurred to traditional small fishermen, they were not protective nor defensive to information and were mostly concerned with appropriate information, the time for dialogue is enough. Obstacles tendency to evaluate occurs in critical fishermen.Keyword: conservation, dialogue communication, environmental communication,national park, public sphereABSTRAKProgram konservasi di Taman Nasional Kepulauan Seribu (TNKpS) membutuhkan ruang komunikasi supaya bisa menarik partisipasi kelompok sasaran, untuk itu diperlukan ruang publik bagi warga untuk saling berdialog membicarakan masalah terkait kebijakan konservasi yang ditujukan kepada mereka. Ruang publik sebagai ruang yang bebas dari unsur dominasi politik maupun ekonomi, baik yang bersifat fisik maupun non fisik, aktornya baik yang dikooptasi maupun tidak dikooptasi, dan ruang publik politiknya baik yang autentik maupun tidak autentik. Dalam ruang publik terjadi komunikasi dialogis yang bersifat dua arah. Dialog yang terjadi di ruang publik dilihat dari tiga jenis: dialog teknis, debat dan dialog asli. Dua elemen penting komunikasi dialogis yaitu listening dan understanding. Ada lima kendala dalam komunikasi dialogis: protektif, defensif, kecenderungan mengevaluasi, ekspektasi yang tidak sesuai dan kurangnya waktu. Penelitian berparadigm kritis dengan pendekatan kualitatif ini menggunakan teori kritis Habermas mengenai ruang publik dan teori tindakan komunikatif dalam perspektif komunikasi lingkungan.Kata kunci: komunikasi dialogis, komunikasi lingkungan, konservasi, ruang publik, taman nasional